Earth electrode resistance diagnosis and measurements - Gunnar Sigvaldason 1985- (2024)
This thesis investigates the potential of an aluminum wire coated with semiconducting plastic material (AX-PRO) as a viable alternative to copper wire for use in grounding systems, particularly under Icelandic conditions. Copper has traditionally been the preferred material for grounding due to its excellent conductive properties, but its increasing cost and susceptibility to theft highlight the need for alternative solutions. This study evaluates the performance of AX-PRO wire through a series of measurements, simulations, and calculations, conducted at two distinct locations in Iceland: Hellisheiði power plant and Vatnsleysa in Biskupstunga. The research objectives include determining whether the AX-PRO wire can provide comparable earth resistance to copper, understanding the influence of Iceland’s harsh weather conditions, and assessing the impact of temperature changes on soil resistivity.The methodology encompasses installing both copper and AX-PRO electrodes at the test sites, performing empirical measurements, conducting simulations using advanced software, and calculating expected resistance values based on standard equations. The results indicate a significant difference in earth resistance between copper and AX-PRO, with the aluminum wire taking longer to achieve its full conductive capacity, especially in frozen soil. Over time, as the soil thawed and compacted around the electrodes, the difference decreased. Initially, calculations and simulations did not align with the measurement results, but the gap seemed to narrow significantly as soil resistivity decreased. It appears that the AX-PRO wire, despite initial issues, is a promising option for use as an earth electrode, although careful attention must be paid to its installation and ensuring proper soil compaction around it. Future work involves extending the measurement period to capture seasonal variations more comprehensively. Continued research aims to solidify AX-PRO’s viability in diverse conditions and contribute to the development of more ...